SMEs’ Financing Decision: The Role of Institutional Environments - Tnah, Shen Liang (2017)
This study is to investigate SME’s financing decision between formal bank financing and alternative financing trade credit. To do so, relevant firm-specific factors including firm size, age, profitability, financial transparency and financial obstacle will be studied. Furthermore, the effects of institutional environments on SME’ financing decision will be studied as well. This is done by considering country-specific factors such as credit availability, rule of law and GDP growth. This study focuses on 30,247 sample SMEs from 133 countries. The datasets are obtained from BEEPS. The results indicate that firm size, age, profitability, financial obstacle and rule of law are significant variables in determining SMEs’ financing with bank loan. Meanwhile, firm size, age, financial obstacle and GDP growth are significant variables in determining SMEs’ financing with trade credit. The result shows a positive relationship between rule of law and bank loan. This indicates that a country with higher rule of law can significantly increase the SMEs to finance with bank loan. Whereas, countries without efficient rule of law will significantly decrease SMEs’ financing from bank loan. Besides, the result indicates a negative relationship between GDP growth and trade credit. This implies that during economic recession, SMEs avoid formal bank financing and increase the use of trade credit. Nevertheless, this study finds no evidence to show the significance of credit availability in determining SMEs’ financing decision between bank loan and trade credit. However, the relationships of bank loan and credit availability as well as trade credit and credit availability are consistent with the prior studies. On the other hand, the additional investigations strongly support the existence of non-linear relationships between firm size and bank loan as well as firm age and bank loan. This implies that if firm size and firm age are increasing, they will increase SMEs’ financing with bank loan. However, after reaching its maximum point when firm size or age increases by one additional unit, the marginal effect in bank loan starts to decline.